The virtual token-passing Ethernet implementation and experimental results - Carreiro, Francisco (2004)
This paper presents the design and first experimental results of VTPE (Virtual Token-passing Ethernet). VTPE \nis a deterministic protocol for real-time applications based on shared Ethernet, aimed to be used either in small \nprocessing power processors or in powerful ones. It is based on implicit token rotation similar to the virtual \ntoken-passing used in the P-NET protocol. The VTPE implementation leads to reduced program code, thus \nfitting in small microcontrollers' memory and imposing low communication overhead. \n